IMPROVEMENT OF ORGANIC RED PIGMENT PRODCUTION BY MONASCUS PURPUREUS TISTR3651 USING PATHUMTHANI-1 RICE-BASED MEDIUM IN SUBMERGED AND SOLID-STATE FERMENTATION - TECHAOEI, SURACHAI; JARMKOM, KHEMJIRA; DUMRONGPHUTTIDACHA, THISAKORN; KHOBJAI, WARACHATE (International Journal of Applied Pharmaceutics, 2021)
Objective: This research is to study the production of natural red pigment by Monascus purpureus TISTR3615 in the submerged and solid-state fermentation system using Pathumthani-1 rice as a carbon source. Methods: The antioxidant activity of the red pigment was evaluated in vitro 2,2-diphenyl-1-picrylhydrazyl (DPPH), ABTS radical scavenging assay, and ferric-reducing antioxidant power (FRAP) assay, including total phenolic compound. Results and Discussion: The maximum of red pigment production was 0.55±0.02/ml (OD 680 nm) after incubation at 30°C for 24 days. The antioxidant activity based on inhibition DPPH (%), ABTS radical scavenging activity (%), and FRAP activity (mM Fe2+/g) was 97.80±1.51, 68.64±0.46, and 0.32±0.021, respectively. The total phenolic content was 164.78±2.82 μg GAE/mg. Conclusion: It was estimated that Monascus pigments, leading to nutraceutical and pharmaceutical applications, cosmetic industry, and food industry.